OCEANOGRAPHIC CONDITIONS OF THE SOUTHERN OCEAN ALONG 125°E AND 160°E IN THE AUSTRAL SUMMER OF 1980-1981 (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - MATSUURA, Noboru; MORINAGA, Tsutomu; KATOH, Juichi; SATO, Hiroh; SAOTOME, Yujiro; KASUGA, Isao; MINE, Yuji; KITAZAWA, Akira (1982)
P(論文) departmental bulletin paper